Pengaruh Indikator Makro Ekonomi Terhadap Return Indeks Saham Sektor Keuangan Di Bursa Efek Indonesia Periode 2011-2015 - Agustina, Lusita Dewi; Budiono, Budiono (Media Mahardhika, 2018)
The purpose of this research is to find out the influence of macroeconomic indicators on stock index return of financial sector. Macroeconomic indicators used are inflation, interest rate, exchange rate, money supply (M2), Indonesian crude price, and domestic gold price. Data variable in this research was secondary data obtained from Sucorinvestâs trading application and official website of Bank Indonesia, Badan Pusat Statistik, ESDM Ministry, and PT Antam. This research is using saturation sampling method and the method of data analysis were multiple regression model and analyzed using EViews software version 9. The result indicates that partially, exchange rate have negative significant influence on stock return and money supply have positive significant influence on stock return, meanwhile inflation, interest rate, Indonesian crude price, and domestic gold price have insignificant influence on stock return.